2014
DOI: 10.1002/ep.11918
|View full text |Cite
|
Sign up to set email alerts
|

Industrial estate wastewater treatment using single up‐flow aerobic/anoxic sludge bed (UAASB) bioreactor: A kinetic evaluation study

Abstract: In this study, performance and kinetic analysis of carbon and nutrients removal in an up-flow aerobic/anoxic sludge bed (UAASB) bioreactor for the treatment of an industrial estate wastewater was investigated. The performance of the reactor was evaluated as a function of two variables, including hydraulic retention time (HRT) of 4, 8, and 12 h and aeration time of 40 and 60 min/h. To obtain the kinetic coefficients, mass balance, first-order, second-order, and Stover-Kincannon models were employed. From the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 23 publications
0
11
2
Order By: Relevance
“…However, as shown in Table 5, the K s value in this study is higher compared to the results by Asadi et al (2014), Kaewsuk et al (2010) and Mizzouri and Shaaban (2013), which employ a substrate with more a complicated structure than sewage. Besides, the K s value in this study is significantly higher than that reported by Metcalf and Eddy et al (2003), and is equal to the study by Pala and B€ olükba (2005), who both consider sewage as a substate.…”
Section: Effect Of Reactor H/d Ratio and Olr On Kinetic Coefficients contrasting
confidence: 76%
See 3 more Smart Citations
“…However, as shown in Table 5, the K s value in this study is higher compared to the results by Asadi et al (2014), Kaewsuk et al (2010) and Mizzouri and Shaaban (2013), which employ a substrate with more a complicated structure than sewage. Besides, the K s value in this study is significantly higher than that reported by Metcalf and Eddy et al (2003), and is equal to the study by Pala and B€ olükba (2005), who both consider sewage as a substate.…”
Section: Effect Of Reactor H/d Ratio and Olr On Kinetic Coefficients contrasting
confidence: 76%
“…This result is in line with Kaewsuk et al (2010) for a high K s value, which demonstrated the activeness of aerobic microbial. However, Asadi et al (2014) found that a process or system with a high value of K s is less efficient. Thus, a plot of m max versus K s was plotted (Fig.…”
Section: Effect Of Reactor H/d Ratio and Olr On Kinetic Coefficients mentioning
confidence: 93%
See 2 more Smart Citations
“…This implies that MIW contains readily biodegradable substrates and the bioreactor has substantial COD removal capacity (Asadi et al . ; Guo et al . ).…”
Section: Resultsmentioning
confidence: 99%